Fasting with adrenal insufficiency: Practical guidance for healthcare professionals managing patients on steroids during Ramadan - Hussain,S; Hussain,S; Mohammed,R; Meeran,K; Ghouri,N (Clinical Endocrinology, 2020)
There are limited recommendations for fasting in many chronic diseases such as adrenal insufficiency (AI). Research in such situations highlights potential for complications and need for education for patients with AI undertaking fasting during Ramadan. This article aimed to provide up-to-date guidance for healthcare professionals to educate, discuss and manage patients with AI who are considering fasting in Ramadan and is religiously compatible. Latest guidance on this topic and the evidence base for steroid dosing are reviewed and discussed. Risk stratification for patients with AI and optimal strategies for management, including steroid dosing, are detailed. Our review highlights that patients with AI wishing to fast should undergo a thorough risk assessment ideally several months before Ramadan. ‘High risk’ and ‘Very high risk’ patients should be encouraged to explore alternative options to fasting discussed below. Prior to the commencement of Ramadan, all patients must receive up-to-date education on sick day rules, instructions on when to terminate their fast or abstain from fasting, carry steroid warning information and must have a valid intramuscular (IM) hydrocortisone pack and know how to administer this. Switching patients with AI desiring to fast from multiple daily hydrocortisone replacement to prednisolone 5 mg once daily at dawn (during Suhoor or Sehri) is recommended and discussed. Patients on fludrocortisone for AI should be advised to take their total dose at dawn. We provide practically relevant case-based scenarios to help with the application of this guidance. Future efforts need to focus on healthcare professional awareness and further research in this setting.